A new species of claroteid catfish (Siluriformes: Claroteidae) from the Eocene of Egypt, (Africa) indicates continental differences in tempo of catfish evolution. Issue 3 (4th May 2021) - Murray, Alison M.; Holmes, Robert B.
ABSTRACT: We here describe a fossil catfish from freshwater deposits of the Jbel Qatrani Formation of the Fayum Depression, Egypt, as a new species of an extant genus, † Clarotes eocenicus, sp. nov., in the family Claroteidae. We base this placement on several cranial osteological features, including robust, laterally oriented anterior cornua of the mesethmoid, cranial fontanelle formed in mesethmoid and frontals but not extending into the parieto-supraoccipital, dermal ornamentation of small bumps concentrated on the posterior part of the skull, and supraoccipital crest short and broadly triangular. The material comes from the upper Eocene L-41 locality, which represents deposition in an oxbow lake environment. The new taxon, along with a previously described catfish from Tanzania, indicate that claroteid catfishes were established in both North and East Africa in the Eocene, and, unlike North America, Europe and Asia in which modern genera of catfishes were not present in the Eocene, at least two extant catfish genera had already evolved in the fresh waters of Africa by 45–35 million years ago.